Glanders in Animals: A Review on Epidemiology, Clinical Presentation, Diagnosis and Countermeasures. Issue 3 (27th May 2012) - Khan, I.; Wieler, L. H.; Melzer, F.; Elschner, M. C.; Muhammad, G.; Ali, S.; Sprague, L. D.; Neubauer, H.; Saqib, M.
Summary Glanders or farcy, caused by Burkholderia mallei, is an infectious and zoonotic disease of solipeds. Horses, donkeys and mules are the only known natural reservoir of B. mallei. Although glanders has been eradicated from most countries, it has regained the status of a re‐emerging disease because of the numerous recent outbreaks. Pre‐symptomatic or carrier animals are the potential source of infection for the healthy equine population and play a crucial role in the spreading of the infectious agent. Glanders is characterized by ulcerating nodular lesions of the skin and mucous membrane. Generalized symptoms include fever, malaise, depression, cough, anorexia and weight loss. Burkholderia mallei can invade its host through mucous membranes, gastrointestinal tract and the integument. Its virulence mechanisms and pathogenesis are not yet completely understood. A major problem when using serological tests for diagnosing glanders is the occurrence of false‐positive and false‐negative results leading to difficulties in international trade with equids and to the spread of glanders to disease‐free regions. Moreover, poor tests critically result in poor control of disease. These tests are not only incapable of discriminating between B. mallei and B. pseudomallei antibodies, they are also unable to differentiate between malleinized and naturally infected animals. Combined use of both serological and molecular detection methods increases the detection rate of glanders. Countermeasures against glanders include early detection of disease in susceptible animals, stringent quarantine measures, testing and safe destruction of infected carcasses, adequate compensation to the animal owners, disinfection of infected premises and awareness about glanders and the zoonotic implications through veterinary extension services. An account of the clinical picture and successful experimental therapy of spontaneous equine glanders is also given.